Lactobacillus delbrueckii subsp. bulgaricus 1.0207 Exopolysaccharides Attenuate Hydrogen Peroxide-Induced Oxidative Stress Damage in IPEC-J2 Cells through the Keap1/Nrf2 Pathway - Deyu Liu; Yingxue Yue; Lijun Ping; Cuicui Sun; Tingting Zheng; Yang Cheng; Guicheng Huo; Bailiang Li (MDPI AG, 2024)
Lactobacillus delbrueckii subsp. bulgaricus (L. bulgaricus) is one of the most commonly employed Lactobacillus in the food industry. Exopolysaccharides (EPS) of Lactobacillus, which are known to exhibit probiotic properties, are secondary metabolites produced during the growth of Lactobacillus. This study identified the structure of the EPS produced by L. bulgaricus 1.0207 and investigated the mitigation of L. bulgaricus 1.0207 EPS on H2O2-induced oxidative stress in IPEC-J2 cells. L. bulgaricus 1.0207 EPS consisted of glucose and galactose and possessed a molecular weight of 4.06 × 104 Da. L. bulgaricus 1.0207 EPS exhibited notable scavenging capacity against DPPH, hydroxyl radicals, superoxide anions, and ABTS radicals. Additionally, L. bulgaricus 1.0207 EPS enhanced cell proliferation, reduced intracellular reactive oxygen species (ROS) accumulation, increased activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and total antioxidant capacity (T-AOC) elevated the relative expression of CAT, SOD, HO-1, NQO1, ZO-1, and Occludin genes. Moreover, L. bulgaricus 1.0207 EPS improved the expression of Nrf2, pNrf2, pNrf2/Nrf2, and Bcl-2 proteins, while decreasing the expression of Keap1, Caspase3, and Bax proteins, with the best effect at a concentration of 100 μg/mL. L. bulgaricus 1.0207 EPS mitigated H2O2-induced oxidative stress injury in IPEC-J2 cells by activating the Keap1/Nrf2 pathway. Meanwhile, L. bulgaricus 1.0207 EPS exhibited the potential to decrease apoptosis and restore the integrity of the gut barrier. The findings establish a theoretical foundation for the development and application of L.bulgaricus 1.0207 and its EPS.